Program Assessment Framework for a Rural Palliative Supportive Service. (January 2013) - Pesut, Barbara; Hooper, Brenda; Sawatzky, Richard; Robinson, Carole A.; Bottorff, Joan L.; Dalhuisen, Miranda
Although there are a number of quality frameworks available for evaluating palliative services, it is necessary to adapt these frameworks to models of care designed for the rural context. The purpose of this paper was to describe the development of a program assessment framework for evaluating a rural palliative supportive service as part of a community-based research project designed to enhance the quality of care for patients and families living with life-limiting chronic illness. A review of key documents from electronic databases and grey literature resulted in the identification of general principles for high-quality palliative care in rural contexts. These principles were then adapted to provide an assessment framework for the evaluation of the rural palliative supportive service. This framework was evaluated and refined using a community-based advisory committee guiding the development of the service. The resulting program assessment framework includes 48 criteria organized under seven themes: embedded within community; palliative care is timely, comprehensive, and continuous; access to palliative care education and experts; effective teamwork and communication; family partnerships; policies and services that support rural capacity and values; and systematic approach for measuring and improving outcomes of care. It is important to identify essential elements for assessing the quality of services designed to improve rural palliative care, taking into account the strengths of rural communities and addressing common challenges. The program assessment framework has potential to increase the likelihood of desired outcomes in palliative care provisions in rural settings and requires further validation.